A linguistic study of contestant self-introductions on video clips in american and vietnamese beauty contests (Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The thesis made an investigation into contestant self-introductions on video clips in American beauty contests and Vietnamese beauty contests to find out the similarities and differences in terms of the semantic features, syntactic features and lexical choice between those two kinds of beauty contests. The research was conducted based on the combination of a variety of methods, namely qualitative, quantitative, descriptive and comparative analysis. 125 samples of American contestant self-introductions and 125 samples of Vietnamese contestant self-introductions were collected from the internet. The findings showed that along with some similarities, there were a number of noticeable differences. The results have provided practical implications in language teaching and learning for English and Vietnamese learners